THE RELATIONSHIP BETWEEN SPIRITUALITY AND RESILIENCE WITH LEVEL OF DEPRESSION IN MEDICAL STUDENTS - Chintia, Chintia; Nugraha, Yudhi; Muktamiroh, Hikmah; Pasiak, Taufiq Fredrik (Universitas Gadjah Mada, 2023)
Background: Depression is a mood disorder that causes distress and affects feelings, thought, and daily activities. Medical students belong to a group that is prone to depression. The high incidence of depression in medical students is caused by stressors in study loads and busy schedules, especially during the COVID-19 pandemic. COVID-19 affects mental health, including a significant increase in depression rates because everyone must adapt to constantly changing situations. Therefore, medical students need the role of spirituality and resilience as protective factors from the occurrence of depression which also allows medical students to rise when faced with difficulties. This study aimed to determine the relationship between spirituality and resilience with the level of depression in medical students.Methods: This research was an observational analytic study with a cross-sectional approach. The research sample was 246 respondents by using the Daily Spiritual Experience Scale (DSES), Connor-Davidson Resilience Scale (CD-RISC), and Beck Depression Inventory (BDI-II) questionnaires.Results: From the results of this study, it was found that the prevalence of depression in respondents was 39%. The bivariate analysis using the Chi-Square test showed a relationship between spirituality with a level of depression (p=0.000) and resilience with a level of depression (p=0.000).Conclusion: The results indicated that there is a significant relationship between spirituality and resilience with a level of depression in medical students. The higher spirituality and resilience, the lower depression level and vice versa. The lower spirituality and resilience, the higher depression level.